Analysis of Overloading Impact on Harmonic Content and Loss of Life in Distribution Transformers - Kartika Tresya M; Alex Fernandes; Welly Okke; Nurmiati Pasra⁠; Samsurizal; Tony Koerniawan (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2026)
In the wake of Indonesia’s accelerating power infrastructure growth, maintaining distribution system integrity is essential to meet the increasing electricity demand from both residential and industrial sectors. This study investigates the operational performance of the PGCE distribution transformer at the Lemah Abang Customer Service Unit (ULP), which experienced severe overloading with a peak loading of 113.82%, exceeding the maximum allowable loading limit of 80% specified in SE No. 0017.E/DIR/2014. The overload condition resulted in excessive thermal stress and a 17% voltage drop, exceeding the permissible service voltage variation specified in SPLN 1:1995. To address these problems, a load-splitting strategy was implemented through the installation of an SNTR insertion transformer. A comparative quantitative (before–after) analysis was conducted using field measurement data to evaluate transformer loading, voltage drop, and transformer loss of life before and after the technical intervention. The results show that the loading of the PGCE distribution transformer was reduced to approximately 76–77%, restoring its operation to within the recommended loading limit. In addition, the voltage drop decreased from 17% to 4.5%, satisfying the service voltage requirement of +5% to −10%. The reduction in transformer loading also lowered thermal stress on the winding insulation, thereby reducing the transformer loss of life and improving asset reliability. These findings demonstrate that load splitting combined with the installation of an insertion transformer is an effective engineering solution for mitigating transformer overloading, improving voltage quality, and extending transformer service life.